ЧИ ІСНУЄ ТВАРИННЕ ЖИТТЯ НА ВЕЛИКИХ ГЛИБИНАХ ЧОРНОГО МОРЯ? - Заїка, В. Є. (Marine Ecological Journal, 2023)
The findings of micro – and meiobenthic eukaryotes representatives at the Black sea deep bottom have been discussed. These findings are unusual for the hydrogen sulfide infected zone. They are in contradiction to two ideas; 1) about absence of life except bacterial, at the Black sea depths, and 2) about impossible life in environment containing hydrogen sulfide. Short history of the Black sea depths studies has been given. Commentaries to N. G. Sergeeva findings are given. There are given the reasons, why these findings can not be cadavres, brought from the upper aerated part of the sea. There is given as well the review of literature on eukaryotes findings in other anoxic biotopes, containing hydrogen sulfide and the data on meiobenthos animals’ strategy in the hydrogen sulfide detoxication.